Digital Afterlives and the Ethics of Postmortem Existence: Rethinking Identity, Autonomy, and Remembrance in the Era of Artificial intelligence - OGAR, Thomas Eneji; AKIBA , Esther E.; ABOKA , George (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The persistence of personhood beyond biological death has emerged as a pressing philosophical and ethical challenge in the digital age. This paper interrogates the ontological and ethical dimensions of postmortem personhood, arguing that the deceased continue to exert influence through relational, memorial, and increasingly, technological means. Drawing on existentialist philosophy (Heidegger, Sartre), ethics (Levinas, Blanchot), and contemporary thanatology, we challenge the Western binary of alive/dead by demonstrating how cultural practices (ancestor veneration, digital memorials) and emerging technologies (AI avatars, cryonics) sustain the dead as active participants in social and moral life. We identify key tensions in postmortem autonomy, consent, and commodification, particularly as digital afterlife technologies outpace legal and ethical frameworks. Ultimately, we propose a process-relational model of personhood that accommodates dynamic, multi-substrate persistence while advocating for ethical stewardship of digital remains. This framework addresses gaps in existentialist and metaphysical accounts, offering a nuanced approach to postmortem personhood that balances technological possibilities with respect for human dignity.